EJIDOS-PRIORITIZATION OF CRITERIA ON PUBLIC GOODS: THE CASE OF RURAL ROADS - Morales-Flores, Francisco Javier; Martín-Fernández Susana; Cadena-Íñiguez Jorge (Revista Mexicana de Ciencias Agrícolas, 2018)
Public participation in the design of public policies is a recurring theme in the exercise of authority. This paper presents a model of participation of rural society, integrating the views of beneficiaries in the maintenance of rural roads, through an analytical hierarchy process, evaluating the importance of economic, social and environmental criteria. The results indicated that, the preferences of the residents to maintaining a road, focused on the practical benefits of having a way to transit: higher learning for young people and children and, a better access to social services, mainly. Public participation is an exercise of citizenship as a right of residence.